Analisis penyebab,social adjustment, dan dukungan sekolah terhadap siswa slow learner di SDN 1 Ngulakan - Taufik Muhtarom; Puput Cahyani (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to obtain information and an overview of causal factors, forms of social adjustment, and school social support for slow learner students participating in grade IV SDN 1 Ngulakan. This research uses qualitative methods. Data collection uses techniques in the form of observation, interviews, and documentation. Data sources were obtained from principals, class teachers, shadow teachers, parents, friends, and slow-learner students as research subjects. Data analysis techniques use Miles and Huberman's model, including data collection, reduction, presentation, and conclusion. The data were checked for the data's validity using source and method triangulation. The results of this study show that: (1) Factors causing slow learner students are influenced by non-hereditary biological factors, such as suboptimal growth and development when toddlers and environmental factors, such as lack of supporting facilities provided by parents; (2) The social adjustment shown by slow learner students at SDN 1 Ngulakan is that slow learner students can interact and adapt to groups at school. However, slow learner students still show high individual attitudes, such as being more fun on their own and less focused on learning; (3) The form of support provided by the school for slow learner students is in the form of assistance from teachers, providing information such as instilling good behavior, providing special scholarships, providing facilities and providing motivation.